Relationship between the 30-second Wingate test and characteristics of isometric and explosive leg strength in young subjects - Arslan, Cengiz (My University, 2005)
The aim of this study was to investigate a possible relation between power performance of the Wingate test (WT) and isometric leg strength (ILS) and explosive leg strength (ELS) characteristics in young men and women with different physical fitness levels. A total of 166 subjects, including 98 young men and 68 young women, were included in the study. The subjects were divided into a regular exercise group and a sedentary group. The physical and body mass index characteristics of the subjects were not different, and they had not taken part in the directed jumping. When the regular exercise and sedentary groups were considered together with men, women, and total population groups, no significant correlation existed between WT anaerobic fatigue index and ILS and ELS (p > 0.05), but significant positive correlations existed among peak power, peak power per weight, mean power, mean power per weight, and WT power, which were recorded in 5-second intervals (p < 0.001). Although the 5-second WT parameters were significantly correlated with ILS and ELS for the first 15-second period, this correlation was more pronounced for the last 15 seconds for all groups (p < 0.01). As a result, this study indicated that regular physical activity has a positive significant relation on WT power, ILS, and ELS in both sedentary men and women and those engaged in regular sports activities. © 2005 National Strength & Conditioning Association.
Keywords: Explosive strength; Isometric strength; Leg strength; Power; Wingate test